Progressive Decrease in N-Acetylaspartate/Creatine Ratio in a Teenager with Type 1 Diabetes and Repeated Episodes of Ketoacidosis without Clinically Apparent Cerebral Edema: Evidence for Permanent Brain Injury - Wootton-Gorges, S.L. (AJNR Am J Neuroradiol, 2010)
Recent data suggest that DKA may contribute to cognitive impairment in children with type 1 DM. We measured the NAA/Cr ratio in a teenager during and following 2 separate episodes of DKA without clinically apparent cerebral edema. The NAA/Cr ratio decreased during DKA and improved following recovery. However, the NAA/Cr value was lower after the second episode of DKA (1.76) than after the first (1.97). These findings provide support for the hypothesis that neuronal injury may result from DKA.